Peran Mediasi Motivasi Ekstrinsik Pada Pengaruh Kepemimpinan dan Pengawasan Terhadap Kinerja Guru Muhammadiyah Kota Binjai - Zawil Huda Mustaid (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
Teacher performance is the result achieved by a teacher in carrying out the tasks and responsibilities that have been assigned to him. One of High performance teacher is shown by professionalism of teacher which consist of four competencies including professional Competence, Pedagogic Competence, Personality and social Competence. Pedagogic Competence is one of type competence that absolutely needs to be mastered for teacher. This study was conducted to examine the role of extrinsic. Motivation on the effects of leadership and supervision on teacher performance in the Muhammadiyah School of Binjai. The population of this study was 125 people with a total sample of  98 respondents and the data collection technique was carried out using a questionnaire with distribution method and processed by the SEM-PLS data processor 3. Results of the study indicate that Extrinsic Leadership and Motivation Significantly Determined Performance, Oversight has a significant effect on Extrinsic Motivation. Leadership Has No Significant Effect on Extrinsic Motivation. Supervision does not determine Significance on Performance. Leadership on Performance through Extrinsic Motivation has no significant effect and Supervision on Performance through Extrinsic Motivation has a significant effect